Clinical outcomes of older patients with AML receiving hypomethylating agents: a large population-based study in the United States - Amer M. Zeidan; Rong Wang; Xiaoyi Wang; Rory M. Shallis; Nikolai A. Podoltsev; Jan Philipp Bewersdorf; Scott F. Huntington; Natalia Neparidze; Smith Giri; Steven D. Gore; Amy J. Davidoff; Xiaomei Ma (2020)
Abstract The hypomethylating agents (HMAs) azacitidine and decitabine have been the de facto standard of care for patients with acute myeloid leukemia (AML) who are unfit for intensive therapy. Using the Surveillance, Epidemiology, and End Results-Medicare linked database, we identified 2263 older adults (age ≥66 years) diagnosed with AML during 2005-2015 who received a first-line HMA; 1154 (51%) received azacitidine, and 1109 (49%) received decitabine. Median survival from diagnosis was 7.1 and 8.2 months (P < .01) for azacitidine- and decitabine-treated patients, respectively. Mortality risk was higher with azacitidine vs decitabine (hazard ratio [HR], 1.11; 95% confidence interval [CI], 1.01-1.21; P = .02). The findings were similar when evaluating only patients completing ≥4 cycles (42% of patients treated with either azacitidine or decitabine). These findings lost significance when evaluating those completing a standard 7-day schedule of azacitidine (34%) vs 5-day schedule for decitabine (66%) (HR, 0.95; 95% CI, 0.83-1.08; P = .43). Red blood cell (RBC) transfusion independence (TI) was achieved in one-third of patients with no difference between the 2 HMAs. In conclusion, the majority of older AML patients did not receive the minimum of 4 cycles of HMA often needed to elicit clinical benefit. We observed no clinically meaningful differences between azacitidine- and decitabine-treated patients in their achievement of RBC TI or survival.